Water Quality Monitoring: A Panacea for Sustainable Aquaculture and Economic Development in Nigeria - Edojarievwen, Uvietobore Tennyson; Chukwurah, Augustine Ikechukwu; Emetulu, Victor; Uruh, Kesena; Onoriasakpobare, Felix Omamuyovwe; Umueni, Elizabeth Uchenna (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Regular water quality monitoring is essential to the sustainability and efficiency of aquaculture systems in Nigeria, where the sector significantly boosts the country's GDP. This study explores how effective water quality monitoring could enhance aquaculture operations in order to address the problems facing the sector that threaten the long-term viability of fish farming and economic growth. The study focused on key water parameters like pH, temperature, turbidity, and soluble oxygen that directly affect fish health, growth rates, and total farm productivity. The study argues that sustaining healthy aquatic ecosystems, increasing fish productivity and guaranteeing the long-term sustainability of the aquaculture sector all depend on routine and efficient water quality monitoring. The study comes to the conclusion that modern water quality management techniques, cutting-edge technology, government support, and strong legislative frameworks are all necessary to improve aquaculture's sustainability, which has the potential to greatly increase food security, reduce poverty and boost Nigeria's economy.